A Longitudinal Study on the Emotional Impact Cause by the COVID-19 Pandemic Quarantine on General Population - Canet-Juric, Lorena; Andrés, María Laura; del Valle, Macarena; López-Morales, Hernán; Poó, Fernando; Galli, Juan Ignacio; Yerro, Matías; Urquijo, Sebastián (Frontiers in Psychology, 2020)
COVID-19 pandemic represents, not only a public physical health emergency, but a mental health serious problem as well. However, little is known about the psychological impact of the quarantine during this pandemic. The aim of this study is to assess the emotional impact of the lockdown measures imposed by the Argentinian government to fight the virus. For this, a survey was distributed on social network. We surveyed the Argentinian general population twice: two days after the mandatory quarantine started, and two weeks later. Anxiety levels were assessed using the State-Trait Anxiety Inventory; depressive symptoms were assessed using the Beck Depression Inventory-II; and affect was assessed using the Positive and Negative Affect Scale. A total of 6057 people answered both surveys. In addition, different socio-demographic factors were considered, such as risk factors for COVID-19, age, gender, educational level, variation in family income due to quarantine, number of children, whether they have older adults in charge or not and the number of hours viewing information about COVID-19. Statistically significant variations were observed between the two measures. The effect size, however, was very small. Depression tends to increase slightly, while levels of anxiety and affect (positive and negative) tend to decrease. Also, some slight differences related to the socio-demographic factors were found. Findings suggests that sustaining the lockdown measures could have a greater effect on mental health in the long term. It is necessary to continue monitoring emotional distress and other related mental health problems on the general population. It is also necessary to create programs aimed at promoting mental health, and to distribute information about it.